If a , b , c > 0 are such that a + b + c = 1 ,find the maximum value of a b + b c + c a .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Shortcut for jee.
In about ~97% , minima is attained when all the numbers are equal.( Bcos A.M = G.M, when numbers are equal)
Log in to reply
Just remember that equality does not always give extrema. It happens in a lot of questions but not in all.
I did same
We have a + b + c = 1 . ⟹ ( a + b + c ) 2 = 1 ⟹ a 2 + b 2 + c 2 + 2 a b + 2 b c + 2 c a = 1 ⟹ a 2 + b 2 + c 2 − a b − b c − c a + 3 a b + 3 b c + 3 c a = 1 ⟹ 2 1 [ ( a − b ) 2 + ( b − c ) 2 + ( c − a ) 2 ] + 3 ( a b + b c + c a ) = 1
3 ( a b + b c + c a ) will be maximum when 2 1 [ ( a − b ) 2 + ( b − c ) 2 + ( c − a ) 2 ] is minimum that is: 2 1 [ ( a − b ) 2 + ( b − c ) 2 + ( c − a ) 2 ] = 0 . ∴ max ( a b + b c + c a = 3 1 )
The problem is symmetrical in all three variables. The boundary, where one or more of the variables are zero, gives low value of the sum of products. So the maximum is where the variables are the largest possible. The only symmetrical solution for that is a = b = c = 3 1 . This gives the sum of the products as 9 1 + 9 1 + 9 1 = 3 1 .
Problem Loading...
Note Loading...
Set Loading...
a 2 + b 2 + c 2 ⩾ a b + b c + c a
⇒ ( a + b + c ) 2 ⩾ 3 ( a b + b c + c a )
⇒ 1 ⩾ 3 ( a b + b c + c a )
⇒ 3 1 ⩾ a b + b c + c a
Therefore, the maximum value of the expression is 3 1 .